My Korean deli : risking it all for a convenience store - Howe, Ben Ryder (New York : Picador., 2012)
A former senior editor of "The Paris Review" recounts his participation in a family effort to buy and run a Korean convenience store for his in-laws, a pursuit that raised issues about work and family while he shuttled between two divergent cultural arenas.
Keywords: Howe, Ben Ryder; Convenience stores -- New York (State) -- New York; Delicatessens -- New York (State) -- New York; Korean American business enterprises -- New York (State) -- New York; Businesspeople -- New York (State) -- New York